The quality evaluation of Wady Eqab wastewater in north of Mosul city for Irrigation - Abdul-Aziz Y. T. Al-Saffawi; Alaa. T. H. Al-Maathi (Tikrit Journal of Pure Science, 2023)
The quality of Wady Eqab waste water has been studied as on of main resources of Tigris river pollution in the north of Mosul city,  the chemical and physical investigation have conducted according to international standards methods, also estimated the irrigation parameters and water quality index (WQI) of the water samples which taken from different sites in Wady Eqab to know   the pollution degree and effects of waste water in Tigris river  in the north of Mosul city.